Waste assimilative capacity of coastal waters along Mumbai mega city, west coast of India using MIKE-21 and WASP simulation models - Vishnuradhan, Renjith; Vethamony, Ponnumony; Zainudin, Zaki; Vinod Kumar, Kumar (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2014)
Coastal waters are the ultimate receivers of the organic waste materials generated by upstream cities and towns. This waste can cause dissolved oxygen depletion due to increased oxygen demand, affecting the natural ability of water bodies to withstand certain amount of pollution - the Waste Assimilative Capacity. The pollution load (Biochemical Oxygen Demand) calculated using the Population Equivalent value of 0.225 m3/day for the present Mumbai population of 13 million is 731,250 kg/day. Simulations using MIKE-21 and WASP models along with the observed water quality data as well as current meter data indicated that the coastal waters can withstand the present pollution load since the simulated Biochemical Oxygen Demand was with in the range of 0.2-1.5 mg/L, the National Standard limits. A projected population increase exceeded the target BOD value of 2 mg/L, indicating the deterioration of ambient quality of coastal waters. Waste Assimilative Capacity studies are crucial in the present-day regional, as well as global issues, such as population explosion, water shortage and climate change.